The Expression Profile and Prognostic Values of EPHA Family Members in Breast Cancer - Zhang, Xixun (Frontiers in Oncology, 2021)
Background: EphAs are a class of ephrin receptors that belong to the membrane-bound receptor tyrosine kinases group. Accumulating experimental evidence has shown that the EphA family is involved in tumor progression, namely in cell proliferation, invasiveness and metastasis. EphAs are a promising target for anticancer therapy. However, their role in breast cancer (BC) is still not well understood. Materials and Methods: We used a series of bioinformatic approaches to analyze the expression of the EphA family members and investigate their prognostic value in BC. Results: Lower expression levels of EphA2, EphA3, EphA4, EphA5, and EphA7 and higher expression levels of EphA10 were found in BC tissues compared to those in normal tissues. The expression levels of the EphA family genes were correlated with molecular subtyping but not with tumor stage. High expression levels of most EphAs indicated a better prognosis in BC. Conclusions: This study suggested that EphA2, EphA3, EphA4, and EphA5 can act as tumor-inhibiting factors as well as biomarkers for the prognosis of BC.